A Foreign Familiarity - Trieneke, Gastmeier (Anthropologica, 2018)
Growing up in Canada of Jamaican Canadian heritage, my racial identity was always called into question. Given that most of my Jamaican family remained in the Caribbean, I felt disconnected from that side of my heritage and in many ways imagined myself as disenfranchised from my own Jamaican identity. This isolation was reinforced by my ability to “pass” and by the constant critique of my “visible identity” by outsiders. While spending three months in Jamaica as a second-generation individual returning to the Caribbean, I was able to reflect on and investigate my family history, learn about my alternative reality, and come to encounter my Jamaican self and broader plurality of identities.